Diversity of plasmids and plasmid-encoded phenotypic traits in Xanthomonas campestris pv. Vesicatoria - Canteros, Blanca Isabel (University of Florida. The Graduate School, 2020)
Tesis para obtener el grado de Doctor of Philosophy, de la University of Florida (Estados Unidos), en 1990